Cigarette Consumer and Poverty in Indonesia - Margareth, Ruth Fenny; Novianti, Tanti; Pasaribu, Syamsul Hidayat (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Poverty is still a social phenomenon that always exists in every developing country, including Indonesia. The purpose of this study is to describe the condition of cigarette consumers and poverty in Indonesia and to analyze the factors that influence poverty in Indonesia. The method used is descriptive analysis and panel data analysis with 18 provinces in Indonesia in 2015-2019. The results of this study indicate that NTT Province is the province with the highest poverty rate. The variable of cigarette consumers has a negative influence on poverty which is dominated by the Province of Lampung. However, this study contradicts the research of Supriadi and Rusyiana (2018) where poor households that have household members who smoke consume relatively less rice on average than households that do not have household members who smoke, whether they are in the poor category or not. The results of the static panel data show that the factors that affect poverty in Indonesia are income per capita(PDRB per capita), unemployment (TPT), means years school (RLS), while the dynamic panel shows that the factors that influence poverty are cigarette consumer (PMP) and mean years school (RLS).